2012
DOI: 10.21236/ada582390
|View full text |Cite
|
Sign up to set email alerts
|

Sweetening Android Lemon Markets: Measuring and Curbing Malware in Application Marketplaces

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Vidas and Christin has investigated applications from alternative markets and compared them to applications from the official market [22]. They have found that certain alternative markets almost exclusively distribute repackaged applications containing malware.…”
Section: B Dynamic Analysismentioning
confidence: 99%
“…Vidas and Christin has investigated applications from alternative markets and compared them to applications from the official market [22]. They have found that certain alternative markets almost exclusively distribute repackaged applications containing malware.…”
Section: B Dynamic Analysismentioning
confidence: 99%
“…End-users get victimized because the applications are desirable to execute. Most users do not check if the application that they want to install does not have a replica [13]. And many fail to check the installation link was emailed to them.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…The way to a secure App market is by performing a verification protocol that they proposed [13]. They called their method "AppIntegrity," which they claims a proof-of-concept implementation.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…In particular, as miscreants discover that mobile devices can be targeted and exploited for financial gain, new forms of malware are created to do so. Some mobile malware is designed to work in tandem with PC-oriented malware while other focuses on mobile devices exclusively [18,36,40].…”
Section: Introductionmentioning
confidence: 99%